Influence of clinical suspicion on CT accuracy of acute mesenteric ischemia: Retrospective study of 362 patients. Issue 138 (May 2021) - Anglaret, S.; Dallongeville, A.; Beaussier, H.; Touloupas, C.; Boulay, I.; Tardivel, A.M.; Béranger, S.; Silvera, S.; Chatellier, G.; Ronot, M.; Zins, M.
Highlights: Clinical examination and lab test are not adapted for accurate diagnosis of AMI. Triple phase CT can be obtained even in patients without clinical suspicion of AMI. CT accuracy for AMI was not different in patients with or without clinical suspicion. Abstract: Purpose: Acute mesenteric ischemia (AMI) may be underdiagnosed when not clinically suspected before CT is performed. We assessed the influence of a clinical suspicion of AMI on the CT accuracy. Method: This retrospective single-centre study included patients who underwent CT in 2014–2019 and had clinically suspected AMI and/or confirmed AMI. CT protocols were adapted based on each patient's presentation and on findings from unenhanced images. The CT protocol was considered optimal for AMI when it included arterial and portal venous phases. CT protocols, accuracy of reports, and outcomes were compared between the groups with and without suspected AMI before CT. Results: Of the 375 events, 337 (90 %) were suspected AMI and 66 (18 %) were AMI, including 28 (42 %) with and 38 without suspected AMI. These two groups did not differ significantly regarding the medical history, clinical presentation, or laboratory tests. The CT protocol was more often optimal for AMI in the group with suspected AMI (26/28 [93 %] vs. 28/38 [74 %], p = 0.046). Diagnostic accuracy was not different between groups with and without suspected AMI (26/28 [93 %] vs. 34/38 [90 %], p = 1.00). However, it was lower in the group without suspicion of AMI when the CT protocol was not optimal for AMI (27/28 [96 %] vs 7/10 [70 %], p = 0.048). Conclusions: The negative influence of not clinically suspecting AMI can be mitigated by using a tailored CT protocol.